RFID Control System for the Embarkation/Disembarkation of Passengers and Vehicles on/from Ferries - Mišković, Toni; Ristov, Pančo; Markić, Zvonko (Transactions on Maritime Science, 2016)
Radio-frequency identification (RFID) is a technology which provides automatic identification and real time data acquisition capabilities without requiring additional human resources. This paper presents a control system for the embarkation/ disembarkation of passengers and vehicles on/from ferries, supported by RFID technology. A basic model of a RFID control system is developed to introduce the notion of RFID as a technology capable of access control with certain technical constraints. The ticket check-in process, made automatic by simple entry of a tag into the field of a RFID reader, increases the flow of passengers and vehicles, reduces port congestion, eliminates the possibility of boarding the wrong (by destination) ferry, and significantly reduces the number of cash payments.